The influence of recruitment organizational culture and motivation on employee performance in class ii port health office Banten - Ria Rahmasuci (Enrichment : Journal of Management, 2023)
In an institution the importance of employee performance as a standard for an institution can be assessed as good. The performance appraisal that occurred at the Banten Class II Port Health Office has decreased due to various factors. The need to increase this performance needs to be seen its effect on several variables, namely recruitment, organizational culture, and motivation that can improve employee performance in achieving organizational goals. The purpose of this study was to measure the effect of recruitment, organizational culture and motivation on employee performance at Class II Port Health Office Banten. Superiors in this study was to measure the effect of recruitment, organizational culture and motivation on employee performance at Class II Banten Port Health OfficE. The research method is quantitative and uses a questionnaire with an ordinal scale of 1-10 points. Sampling technique with saturated sampling method of 70 samples. The research findings explain that there is an influence of recruitment, organizational culture and motivation on performance employees at the Banten Class II Port Health Office. The research findings explain that there is an influence of recruitment, organizational culture and motivation on performance employees at the Banten Class II Port Health Office.